1973
DOI: 10.1007/bf01250421
|View full text |Cite|
|
Sign up to set email alerts
|

The nucleic acid of infectious bronchitis virus

Abstract: SummaryThe nucleic acid of infectious bronchitis virus (IBV), like that of other enveloped viruses, consists of discontinuous single stranded RNA. However, unlike many other viruses, there is extreme heterogeneity in the sizes of the I~NA fragments, as revealed by centrifugation in sucrose gradients or electrophoresis in polyacrylamide gels. Two principal classes of I~NA fragments are present: ~) A larger class comprising 74.9--85.4 per cent of total RNA and consisting of fragments having molecular weights ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

1975
1975
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 27 publications
2
12
0
Order By: Relevance
“…Previous reports have shown that the nucleic acid of IBV is RNA [4,5] although there is some discrepancy as to the size of this RNA. Tannock [4] analysed phenol-extracted IBV RNA and showed it to consist of extremely heterogeneous RNA fragments, while Watkins et al [S] have shown that the IBVgenome extracted with 1% SDS at 60°C is a single large mol.…”
Section: Wimentioning
confidence: 89%
See 1 more Smart Citation
“…Previous reports have shown that the nucleic acid of IBV is RNA [4,5] although there is some discrepancy as to the size of this RNA. Tannock [4] analysed phenol-extracted IBV RNA and showed it to consist of extremely heterogeneous RNA fragments, while Watkins et al [S] have shown that the IBVgenome extracted with 1% SDS at 60°C is a single large mol.…”
Section: Wimentioning
confidence: 89%
“…Tannock [4] analysed phenol-extracted IBV RNA and showed it to consist of extremely heterogeneous RNA fragments, while Watkins et al [S] have shown that the IBVgenome extracted with 1% SDS at 60°C is a single large mol. wt (9.0 X 106) RNA species.…”
Section: Wimentioning
confidence: 99%
“…Direct confirmation of the RNA content of infectious bronchitis virus (IBV) has now been provided by T ann ock [17] and W a tk ins et al [18] and of HCV by J.C. H ierh o lzer (reported by T yrrell et al [8]). However, at tempts to resolve the structure of the internal component of the se viruses have, until now, proven unsuccessful.…”
Section: Discussionmentioning
confidence: 99%
“…Phenol (Fisher, reagent grade) for RNA extraction was twice distilled. Yeast carrier RNA was prepared according to the method of Tannock (1973 Virus was released from cells in the suspension by freezing and thawing four times, and particulate matter was removed by centrifuging at 5,000 g in a Spinco 40 rotor for 20 min. The supernatant was retained in an ice bath while the pellet was resuspended in PBS to 20% of the original volume and recentrifuged; both supernatants were then combined for purification.…”
Section: Methodsmentioning
confidence: 99%
“…The Coronaviridae were described as a separate taxonomic group by Almeida et al (1968) but, despite their ubiquity and economic importance, few biophysical characterization studies have been reported. The RNA of avian infectious bronchitis virus (IBV) was first described by Tannock (1973), who obtained from purified virions a highly heterogeneous array of RNA fragments using a phenol-sodium dodecyl sulfate (SDS) extraction procedure. Fragments ranged in molecular weight from 0.5 x lo6 to more than 3.0 x 106; a smaller, more homogeneous class of a size similar to ribosomal 4 S RNA was also present.…”
Section: Introductionmentioning
confidence: 99%